2019
DOI: 10.7554/elife.46592
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 1 family proteins promote Slimb-dependent Expanded degradation

Abstract: Hippo signalling integrates diverse stimuli related to epithelial architecture to regulate tissue growth and cell fate decisions. The Hippo kinase cascade represses the growth-promoting transcription co-activator Yorkie. The FERM protein Expanded is one of the main upstream Hippo signalling regulators in Drosophila as it promotes Hippo kinase signalling and directly inhibits Yorkie. To fulfil its function, Expanded is recruited to the plasma membrane by the polarity protein Crumbs. However, Crumbs-mediated rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…To understand how Mer regulates Kib levels, we set out to develop a simpler approach to uncouple Kib protein abundance from its transcriptional regulation. Recently, the ubiquitin 63E promoter was used to drive expression of other Hpo pathway components to study their post-translational regulation ( Aerne et al, 2015 ; Fulford et al, 2019 ), based on the assumption that the ubiquitin promoter is not regulated by Yki activity. Therefore, we made a transgenic fly line ectopically expressing Kib-GFP-FLAG under control of the ubiquitin promoter (Ubi>Kib-GFP) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how Mer regulates Kib levels, we set out to develop a simpler approach to uncouple Kib protein abundance from its transcriptional regulation. Recently, the ubiquitin 63E promoter was used to drive expression of other Hpo pathway components to study their post-translational regulation ( Aerne et al, 2015 ; Fulford et al, 2019 ), based on the assumption that the ubiquitin promoter is not regulated by Yki activity. Therefore, we made a transgenic fly line ectopically expressing Kib-GFP-FLAG under control of the ubiquitin promoter (Ubi>Kib-GFP) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple Hpo pathway components are also regulated post-translationally. For example, Crb promotes Ex ubiquitination via Skip/Cullin/F-box Slimb (SCF Slimb ) E3 ubiquitin ligase complex, which leads to Ex degradation ( Ribeiro et al, 2014 ; Fulford et al, 2019 ). Similarly, Ds and Dachs levels are downregulated by the SCF Fbxl-7 E3 ubiquitin ligase, and Dachs stability is also influenced by an E3 ubiquitin ligase called Early girl ( Bosch et al, 2014 ; Rodrigues-Campos and Thompson, 2014 ; Misra and Irvine, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…circRNAs are highly stable molecules and have been demonstrated to play important roles in ageing [41] and age-related diseases [42,43]. Additionally, six source genes of circRNAs were related to fruit y ageing, including asator (short-lived, Asator GD7323 ) [44], dad (short-lived, Dad GD1335 ) [45], gish (short-lived, gish GD10588 ) [44,46], pan (short-lived, pan ΔN.UAS ) [47,48], psq (long-lived, psq BG01031 ) [49,50], and arm (short-lived, arm S10.UAS.Tag:MYC ) [51]. Previous studies have demonstrated that lncRNAs are also involved in the regulation of ageing and multiple diseases [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…To understand how Mer regulates Kib levels, we set out to develop a simpler approach to uncouple Kib protein abundance from its transcriptional regulation. Recently, the ubiquitin 63E promoter was used to drive expression of other Hippo pathway components to study their post-translational regulation (Aerne et al, 2015;Fulford et al, 2019), based on the assumption that the ubiquitin promoter is not regulated by Yki activity. Therefore, we made a transgenic fly line ectopically expressing Kibra-GFP-FLAG under control of the ubiquitin promoter (Ubi>Kib-GFP) ( Fig.…”
Section: Transcriptional Feedback Is Insufficient To Explain the Incrmentioning
confidence: 99%
“…Multiple Hippo pathway components are also regulated post-translationally. For example, Crb promotes Ex ubiquitination via Skip/Cullin/F-box Slimb (SCF Slimb ) E3 ubiquitin ligase complex, which leads to Ex degradation (Ribeiro et al, 2014;Fulford et al, 2019). Similarly, Ds and Dachs levels are downregulated by the SCF E3 ubiquitin ligase, and Dachs stability is also influenced by an E3 ubiquitin ligase called Early girl (Rodrigues-Campos and Thompson, 2014;Misra and Irvine, 2019).…”
Section: Introductionmentioning
confidence: 99%